Genetic progress in Argentine bread wheat varieties released between 1918 and 2011: Changes in physiological and numerical yield components - Lo Valvo, Patricio Javier (2018)
The objective of this study is to update the data of genetic progress in bread wheat cultivars released in Argentina from 1918 to 2011 (emphasizing the last 20 years) characterizing different agronomic traits of interest for breeders. Experiments were carried out with a wide range of bread wheat cultivars and conducted under field conditions without nutritional and water restrictions. Yields showed a significant (R2 = 0.68) tri-linear trend when associated with the cultivar's year of release. Until the 40s, when the first inflection point occurred, the genetic progress in terms of yield was 0.8 kg ha−1 yr−1 (0.02% yr−1). Between 1940 and 1999, yield genetic progress reached its highest value (51 kg ha−1 yr−1; 1.17% yr−1) but changed after 1999 when values became lower compared to the previous period, showing a value of 14 kg ha−1 yr−1 (0.18% yr−1). Changes in grain yield were mostly explained by increases in harvest index and not by those in above-ground biomass. Plant height showed a negative bi-linear trend with the year of release, reaching an inflexion point well before the introgression of semi-dwarfing genes in commercial cultivars. Grain number increased ca. 63% when modern cultivars were compared to older ones, which explains most of the grain yield changes. In contrast to grain number, no significant differences between old and modern cultivars were found for grain weight, with average values of ca. 30 mg grain−1 for all environments explored.